Correlation Between Influenza Virus Replication and ATP6V0C of Trivalent Influenza (TIV) Vaccination in Ferret (Indian Journal of Forensic Medicine & Toxicology, 2020)
Influenza virus infections are a major public health threat. Influenza viruses are associated with highmortality and morbidity worldwide through seasonal epidemics. Vaccination programs are available, butunpredictable antigenic changes in circulating strains require annual modification of seasonal influenzavaccines. Influenza vaccines are given, one of which is a trivalent influenza vaccine (TIV) aimed at theformation of antibodies that are specific to influenza viruses by B cells. In this study TIV vaccination has aneffect in the form of decreasing viral replication in ferret that have been tested with H1N1 and H3N2 viruses.The results of this study are data about viral replication obtained from hemagglutination tests (HA test) andATP6V0C expression with SDS-Page.